Photo-ultrasonic assisted in-situ synthesis of RGO/ Ag2CrO4 photocatalyst with high photocatalytic activity and stability under visible light. (1st November 2018) - Abulizi, Abulikemu; Zhou, Li; Kadeer, Kuerbangnisha; Tursun, Yalkunjan; Talifu, Dilinuer
Abstract: Visible-light-active reduced graphene oxide/ Ag2 CrO4 (RGO/ Ag2 CrO4 ) composites were prepared by a novel photo-ultrasonic assisted reduction process. Compared to single Ag2 CrO4 photocatalyst, as-prepared RGO/ Ag2 CrO4 composites had displayed dramatically enhanced photocatalytic activity toward the degradation of methylene blue (MB) and tetracycline (TC) under visible light illumination (λ > 420 nm). And when the mass ratio of RGO to Ag2 CrO4 was 0.5%, sample showed the most superior photocatalytic activity, with degrading 97.68% and 80.03% of MB and TC in 60 min, respectively, which was about 0.9 times and 2 times higher than that of pure Ag2 CrO4 . The excellent photocatalytic activity was majorly due to the coupling of nano-sized Ag2 CrO4 (6–9 nm) with high electron-conductive RGO, which had boosted charge separation and transfer. Improved photocatalytic stability was mainly ascribed to the fast transferring of photogenerated electrons from Ag2 CrO4 to RGO before the reduction of Ag ions to metallic Ag. This work can provide a more economical and effective method for the exploration of efficient RGO-based photocatalysts.